Recycling process for production of polyamide compounds
By mixing polyamide A with the salt C of dilate and dilate, prepare a polyamide B with a low viscosity and a specific terminal group concentration ratio, solving the recycling of polyamide in the existing technologies to use the molecular weight and mechanical performance The problem of difficulty control has realized the production of high -quality re -cycling for injection molding to use polyamide.
Patent Information
- Application Number
- CN202380045551.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-06-07
- Publication Date
- 2025-01-24
AI Technical Summary
Existing polyamide recycling methods are difficult to control the molecular weight and mechanical properties of polyamides, resulting in difficulty in producing high-quality products.
Polyamide B with low viscosity and specific end group concentration ratio is prepared by melt mixing polyamide A with salt C of diacid and diamine.
This enables the production of recycled polyamide B with good flow properties and melt stability, suitable for injection molding applications.
Smart Images

Figure BDA0005174665540000021 
Figure BDA0005174665540000091 
Figure BDA0005174665540000092
Abstract
Description
[0001] The present invention relates to a process for preparing a polyamide B, which comprises melt mixing a polyamide A with a salt C of a diacid and a diamine, wherein the polyamide B has a lower viscosity value than the polyamide A and has a specific ratio of the ratio of the amino terminal group concentration of polyamide B to the amino terminal group concentration of polyamide A to the ratio of the carboxyl terminal group concentration of polyamide B to the carboxyl terminal group concentration of polyamide A; a polyamide B obtained by the above process; a polyamide B1 composed of polyamide B* and units derived from the diacid and the diamine forming the salt C; a polyamide composition comprising: the polyamide B or the polyamide B1; a filler material (D) and optionally at least one further additive (E); a polymer product comprising the polyamide B, the polyamide B1 or the polyamide composition; use of the polyamide B, the polyamide B1 or the polyamide composition for producing a polymer product; and a process for preparing a polymer product comprising the polyamide B, the polyamide B1 or the polyamide composition. Background Art
[0002] Polyamides (nylons) with high temperature and electrical resistance are considered high-performance plastics and are widely used in the automotive and transportation markets, consumer goods, electrical and electronic applications and fiber production, among others. In the course of environmental measures, material recycling of polyamide waste is gaining increasing importance. Polyamides are a class of compounds suitable for chemical recycling. Chemical recycling via the depolymerization of polyamides is a promising approach to save fossil raw materials in monomer synthesis and to reduce the amount of plastic waste.
[0003] Examples of known recycling methods via depolymerization are described below:
[0004] US 3,069,465 relates to a process for recovering adipic acid and hexamethylenediamine from polyhexamethylene adipamide (PA 66) by continuous hydrolysis of the adipic acid in aqueous sulfuric acid solution.
[0005] U. Cesarek et al., ACS Sustainable Chem. Eng., 2020, 8, 16274-16282 relates to a chemical recycling process for aliphatic polyamides (PA) (PA 66, PA 1010, PA 11 and PA 12), whereby PA is converted only to its constituent monomers even in the presence of reinforcing additives such as carbon fibers and glass fibers. The PA hydrolysis reaction is carried out under microwave irradiation in the presence of HCl as an acid catalyst.
[0006] US5310905 relates to a method for recovering caprolactam from waste polycaprolactam, the method comprising providing an acid of the formula
[0007]
[0008] wherein n is from 0 to 4 and polycaprolactam is charged to an autoclave in an amount of at least one mole of acid per two moles of repeating units of the polymer, the mixture is heated at autogenous pressure or higher for a time sufficient to depolymerize the polymer and form a mixture of caprolactam and 6-alkylamido caproic acid, and the caprolactam is separated from the mixture.
[0009] In the above-mentioned recycling process, the monomers of the corresponding polyamide are recovered. Said monomers can then optionally be polymerized again in the presence of fresh (ie non-recycled) monomers to obtain polyamide.
[0010] In the above-described method, the molecular weight of the polyamide is reduced by adding an acid. However, the molecular weight reduction caused by the acid is difficult to control due to the high reaction rate in the melt and leads to a significant degradation of the mechanical properties. In addition, when polyamide starting materials with unspecified composition and / or initial viscosity are used (e.g. mixed production waste and / or recycled materials), the control of such reactions becomes even more difficult. Therefore, such materials are not used to produce high-quality products, because the target viscosity adjustment would require extensive preliminary studies and test runs.
[0011] However, from an environmental point of view, recycling polyamide by controlled partial depolymerization is advantageous, especially if lower grades of polyamide are required.
[0012] There are methods known in the art involving viscosity regulation / control. However, said methods are not recycling methods of polyamide, but only regulation / control methods.
[0013] EP 3553113 A1 relates to a method for controlling the molecular structure and selective functionalization of polyamides, which method comprises reacting the polyamide with at least two of the following additives: a) a first additive comprising an acid and / or anhydride and preferably a polymer carrier, b) a second additive comprising an oxazoline and / or an amine optionally mixed with a carrier, c) a third additive comprising a compound for chain extension or chain branching optionally mixed with a carrier, wherein the reaction of the polyamide with the at least two additives is operated in such a way that the reaction with one additive is carried out first and then the reaction with the other additive is carried out.
[0014] WO 2018 / 072875 relates to an additive for controlling the viscosity regulation of a polycondensate, the regulator comprising an acid and / or anhydride and a carrier, preferably a polymer carrier, characterized in that the acid and / or anhydride is uniformly distributed in the carrier; a method for preparing the additive; a method for controlling the viscosity regulation of a polycondensate and the use of the additive for controlling the viscosity regulation of a polycondensate.
[0015] DE 4421239 A1 discloses a method for recycling by partial degradation of polyamides. DE 4421239 A1 relates to a method for recycling high molecular weight nylon 6 (polyamide 6), to a repolymer prepared by the method, and to a method for recycling high molecular weight nylon 6 or used plastic parts made of nylon 6, the method using a common depolymerization step in the presence of caprolactam, water and acid to obtain a melt of a defined viscosity level, after removing components insoluble in the low viscosity melt from the melt, repolymerizing or degrading the remaining material to obtain a further processable repolymer or to obtain caprolactam.
[0016] In B. Formisano et al., “Recycling of cast polyamide waste with a twin-screw-extruder”, 24. Stuttgarter Kunststoffkolloquium, uploaded on July 2, 2015 by Christian Bonten, cast polyamide 6 (PA6G) waste is processed into extrudable polyamide by compounding with unspecified suitable additives. Rheological and mechanical analyses show that the use of lubricants is particularly advantageous and that oxidants lead to injection moldable materials with low viscosity.
[0017] FR 3 107 059 A1 relates to a method for processing a polyamide composition intended for recycling, comprising the following steps: (i) providing a mixture comprising a polyamide intended for recycling, a polyamide chain scissioning agent and optionally one or more fillers and / or additives; (ii) kneading the mixture in the molten state to obtain a composition having a target intrinsic viscosity; (iii) recovering the composition obtained in step (ii). Suitable chain scissioning agents are selected from water, carboxylic acids, amino acids and / or mixtures thereof.
[0018] WO 2020 / 041259 A1 relates to a method for reducing the relative viscosity (RV) of a polyamide melt, the method comprising: treating a first polyamide having an RV of 45 or greater with an additive mixture, the additive mixture comprising an organic dicarboxylic acid having a specific particle size distribution and a second polyamide having a specific particle size distribution; and melt-treating the first polyamide treated with the additive mixture.
[0019] However, compared to US 6,187,877 B1 (D1), WO 2011 / 138397 A1 (D2), JP 2001200054A (D3), JP H09 234789A (D4), WO 2018 / 165641 A1 (D5), the subject matter of product claims 11 and 12 and claims 13 to 18 that depend on or refer to product claims 11 and 12 are not considered to be novel.
[0020] US Pat. No. 6,187,877 B1 relates to a process for preparing polymers based on dicarboxylic acids and diamines by polycondensation in an extruder.
[0021] WO 2011 / 138397 A1 relates to a process for preparing a polyamide containing monomer units of 1,4-diaminobutane and an aliphatic linear carboxylic acid, as well as PA-410 obtainable by the process and products prepared therefrom.
[0022] JP 2001 200054A relates to a method for producing nylon 6 copolymers and fibers having good basic dyeability. It has been mentioned that the nylon 6 copolymer is prepared by reacting an aqueous solution of ε-caprolactam containing a salt of a dicarboxylic acid and a diamine and / or an aminocarboxylic acid.
[0023] JP H09 234789 A relates to a method for producing an axially stretched polyamide film. The polyamide is a terpolymer based on ε-caprolactam (85% to 99% by weight), aminododecanoic acid (0.5% to 5% by weight) and an equimolar salt of hexamethylenediamine and adipic acid (0.5% to 10% by weight).
[0024] WO 2018 / 165641 A1 relates to a polyamide composition for forming a wire or cable jacket composition. The polyamide composition includes a component of a polyamide 6 / 66 copolymer formed from substantially randomly distributed caprolactam monomers and hexamethylenediamine monomers.
[0025] An object of the present invention is to provide a process for the recycling of polyamides, in particular for post-industrial and / or post-consumer polyamide waste originating from the extrusion industry, by reducing the molecular weight of the polyamide, making it possible to produce recycled polyamides having good flow properties and sufficient melt stability, in particular for injection molding applications, without requiring complete depolymerization (recovery of monomers) followed by repolymerization of the recovered monomers.
[0026] In order to obtain polyamide compounds which are injection moldable in particular, a process is required which allows a defined and uniform reduction in viscosity and at the same time avoids further degradation of the compound produced.
[0027] This object is achieved by a process for preparing a polyamide B, which comprises melt mixing a polyamide A with a salt C of a diacid and a diamine,
[0028] wherein polyamide B has a lower viscosity value than polyamide A, and
[0029] Wherein, in polyamide B, the ratio of the amino terminal group concentration of polyamide B to the amino terminal group concentration of polyamide A (c NH2B / c NH2A ) and the ratio of the carboxyl terminal group concentration of polyamide B to the carboxyl terminal group concentration of polyamide A (c COOHB / c COOHA ) ratio ((c NH2B / c NH2A ) / (c COOHB / c COOHA )) is 0.8 to 1.2.
[0030] Preferably, (c NH2B / c NH2A ) / (c COOHB / c COOHA ) is 0.9 to 1.1.
[0031] The viscosity number (VN) of the polyamide and polyamide composition according to the invention is measured in sulfuric acid according to EN ISO 307:2019 (0.5% [m / v] polyamide in 96 wt.-% [m / m] sulfuric acid at 25° C.).
[0032] The melt volume flow rate (MVR) of the polyamide according to the invention is measured according to EN EN ISO 1133-1:2011, procedure A.
[0033] The amino terminal group concentration (AEG [meq / kg]) of the polyamide disclosed in the present invention is measured by potentiometric titration of a polyamide-methanol-phenol solution with an aqueous hydrochloric acid solution. The carboxyl terminal group concentration (CEG [meq / kg]) of the polyamide disclosed in the present invention is measured by titration of a polyamide-benzyl alcohol solution with an ethanolic potassium hydroxide solution.
[0034] The object is further achieved by a polyamide B1 consisting of:
[0035] a) 99.00 to 99.99% by weight, preferably 99.10 to 99.90% by weight, of a polyamide B* formed from units selected from one or more diamines in combination with one or more diacids, one or more lactams and mixtures thereof, and
[0036] b) 0.01 to 1% by weight, preferably 0.1 to 0.9% by weight, of units derived from the diacids and diamines which form the salt C,
[0037] wherein the units derived from the diacid and the diamine forming the salt C are different from the units forming the polyamide B*.
[0038] This object is further achieved by a polyamide B obtainable by the process according to the invention, wherein the ratio of the amino end groups of the polyamide B measured by potentiometric titration of a polyamide-methanol-phenol solution with aqueous hydrochloric acid to the carboxyl end groups of the polyamide B measured by titration of a polyamide-benzyl alcohol solution with ethanolic potassium hydroxide is preferably ≥ 0.2, more preferably ≥ 0.40 and most preferably ≥ 0.70.
[0039] The object is further achieved by a polyamide composition comprising:
[0040] (i) a polyamide B or a polyamide B1 according to the invention; and
[0041] (ii) optionally a filler material (D) and
[0042] (iii) optionally at least one further additive (E);
[0043] At least one filler material (D) or one further additive (E) is present therein.
[0044] This object is further achieved by a polymer product, preferably an injection-molded part, comprising a polyamide B, polyamide B1 or polyamide composition according to the invention; by the use of a polyamide B, polyamide B1 or polyamide composition according to the invention for producing a polymer product, in particular an injection-molded part, and by a process for preparing a polymer product, which process comprises converting a polyamide B, polyamide B1 or polyamide composition according to the invention, preferably by a process for preparing a molding, which process comprises injection molding a polyamide B, polyamide B1 or polyamide composition according to the invention.
[0045] The present invention allows to maintain the concentration ratio of the terminal groups (amino groups and carboxylic acid groups) of the starting polyamide (with a deviation of about + / - 20%, preferably about + / - 10%). Thus, the melt stability (MVR over time) of the recycled polyamide is ensured, i.e. the MVR does not increase over time or increases over time by less than 5%, preferably less than 3.5%, more preferably the MVR does not increase over time, which is a prerequisite for the application of recycled polymers, in particular in injection molding, preferably at low concentrations of additives.
[0046] Generally speaking, polyamide B as well as polyamide A may have any ratio of amino end group concentration to carboxyl end group concentration. Suitable ratios are ≥ 0.2, preferably ≥ 0.40, more preferably ≥ 0.70.
[0047] In the process of the present invention, only a small amount of salts of diacids and diamines is required. The "salts of diacids and diamines" mentioned in the present invention may be salts of a single diacid and a single diamine. However, a mixture of two or more diacids and / or a mixture of two or more diamines may also be present in the molten mixture.
[0048] Salts of diacids and diamines
[0049] Preferably, the salts of diacids and diamines are present in an amount of 0.01 to 1 wt.-%, more preferably 0.1 to 0.9 wt.-%, most preferably 0.15 to 0.5 wt.-%, based on polyamide A. The diamines and diacids are preferably present in stoichiometric amounts, with the optional deviation from stoichiometry typically being 5 to 10%. In case the diacid(s) and diamine(s) are not used in the stoichiometric amounts necessary for salt formation, the amounts mentioned relate to the salts formed from the diacid(s) and diamine(s), and an excess of free diacid or diamine may be present in addition to the amounts of salt mentioned.
[0050] The diacid is a dicarboxylic acid. In a preferred embodiment, the diacid is selected from the group consisting of adipic acid, glutaric acid, suberic acid, sebacic acid, dodecanedioic acid, 1,2-cyclohexanedicarboxylic acid or 1,3-cyclohexanedicarboxylic acid, 1,2-benzenedioic acid or 1,3-benzenedioic acid, 1,2-cyclohexanediacetic acid or 1,3-cyclohexanediacetic acid, isophthalic acid, p-(tert-butyl)isophthalic acid, terephthalic acid, azelaic acid, pimelic acid, 4,4'-benzophenone dicarboxylic acid; 2,5-naphthalene dicarboxylic acid or 5-sulfoisophthalic acid or its alkaline salt, and / or mixtures thereof. The preferred diacid is adipic acid.
[0051] In a preferred embodiment, the diamine is selected from the group consisting of hexamethylenediamine, heptamethylenediamine, tetramethylenediamine, pentamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, 2-methylpentamethylenediamine, undecamethylenediamine, dodecamethylenediamine, xylenediamine or isophoronediamine; 2-methylhexamethylenediamine; 3-methylhexamethylenediamine; 2,5-dimethylhexamethylenediamine; 2,2-dimethylpentanediamine; 5-methylnonanediamine; 2,2,4-trimethylhexamethylenediamine and 2,4,4-trimethylhexamethylenediamine; 2,2,7,7-tetramethyloctanediamine; m-xylylenediamine; p-xylylenediamine; diaminodicyclohexylmethane and C2-C16 aliphatic diamines which may be substituted with one or more alkyl groups, and / or mixtures thereof. The preferred diamine is hexamethylenediamine.
[0052] Most preferably, the salt of a diacid and a diamine is hexamethylenediamine adipate.
[0053] Polyamide A and B
[0054] The viscosity values of polyamides A and B are generally not critical, as long as polyamide B has a lower viscosity value than polyamide A.
[0055] The viscosity of polyamide A is preferably 120 cm 3 / g to 250cm 3 / g, more preferably 150cm 3 / g to 220cm 3 / g, most preferably 170cm 3 / g to 210cm 3 / g.
[0056] The viscosity of polyamide B and polyamide B1 is preferably 80 cm 3 / g to 200cm 3 / g, more preferably 100cm 3 / g to 180cm 3 / g, most preferably 120cm 3 / g to 160cm 3 / g. The term "polyamide" generally includes homopolyamides as well as copolyamides.
[0057] Preference is given to semicrystalline or amorphous polyamides or mixtures thereof.
[0058] Examples of these polyamides are polyamides derived from lactams having 7 to 13 ring members, for example polycaprolactam, polycapryllactam and polylaurolactam, such as PA 6, PA 12.
[0059] Further examples are polyamides obtained via the reaction of dicarboxylic acids with diamines.
[0060] Particularly suitable dicarboxylic acids are alkane dicarboxylic acids and aromatic dicarboxylic acids having 6 to 12, in particular 6 to 10, carbon atoms. Merely by way of example, those dicarboxylic acids which may be mentioned here are adipic acid, azelaic acid, sebacic acid, dodecanedioic acid and terephthalic acid and / or isophthalic acid.
[0061] Particularly suitable diamines are alkane diamines having 6 to 12, in particular 6 to 8, carbon atoms, and also meta-xylylenediamine, bis(4-aminophenyl)methane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-aminocyclohexyl)propane and 1,5-diamino-2-methylpentane.
[0062] Suitable polyamides are polyhexamethylene adipamide, polyhexamethylene sebacamide and polycaprolactam, and also PA 6 / 66 copolyamides, in particular those having a proportion of 5 to 95% by weight of caprolactam units (e.g. Polyol from BASF SE). C31).
[0063] Other suitable polyamides are obtainable from ω-aminoalkylnitriles, for example aminocapronitrile (PA 6) and adiponitrile, and hexamethylenediamine (PA 66) in the presence of water by so-called direct polymerization, as described, for example, in DE-A 10313681, EP-A 1198491 and EP 922065.
[0064] Mention may also be made of polyamides obtainable, for example, by condensation of 1,4-diaminobutane with adipic acid at elevated temperature (PA 46) or by condensation of hexamethylenediamine with sebacic acid (PA 610). Processes for the preparation of polyamides of this structure are described, for example, in EP-A 38 094, EP-A 38 582 and EP-A 39 524.
[0065] Other suitable examples are polyamides obtainable by copolymerization of two or more of the abovementioned monomers, and mixtures of two or more polyamides in any desired mixing ratio. Particularly preferred are mixtures of PA 66 with other polyamides, in particular blends of PA 6 and PA 66, and PA 6 / 66 copolyamides and PA 66 / 6 copolyamides.
[0066] Other copolyamides which have proven particularly advantageous are semiaromatic copolyamides such as PA 6 / 6T, PA 6T / 6, PA6T / 66 and PA 66 / 6T, wherein the triamine content of these is preferably less than 0.5% by weight, preferably less than 0.3% by weight (cf. EP-A 299 444). Other high temperature resistant polyamides are known from EP-A 19 94 075 (PA 6T / 6I / MXD6).
[0067] The processes described in EP-A 129 195 and 129 196 can be used for preparing the preferably semiaromatic copolyamides having a low triamine content.
[0068] Other polyamides which have proven to be advantageous are aromatic polyamides such as PA 9T, PA 10T, PA 4T and the copolyamides PA 6I / 6T, PA 6T / 6I.
[0069] Suitable copolyamides consist of:
[0070] A1) 20.0% to 90.0% by weight of units derived from terephthalic acid and hexamethylenediamine,
[0071] A2) 0 to 50.0% by weight of units derived from ε-caprolactam,
[0072] A3) 0 to 80.0% by weight of units derived from adipic acid and hexamethylenediamine,
[0073] A4) 0 to 40.0% by weight of other polyamide-forming monomers,
[0074] The proportion of component A2) or A3) or A4) or a mixture thereof is at least 10.0% by weight.
[0075] Component A1) comprises from 20.0% to 90.0% by weight of units derived from terephthalic acid and hexamethylenediamine.
[0076] Besides the units deriving from terephthalic acid and hexamethylenediamine, the copolyamide optionally comprises units deriving from ε-caprolactam and / or units deriving from adipic acid and hexamethylenediamine and / or units deriving from further polyamide-forming monomers.
[0077] The aromatic dicarboxylic acids A4) contain 8 to 16 carbon atoms. Suitable aromatic dicarboxylic acids include, for example, isophthalic acid, substituted terephthalic acids and isophthalic acid, such as 3-tert-butylisophthalic acid, polycyclic dicarboxylic acids, for example 4,4'-diphenyldicarboxylic acid and 3,3'-diphenyldicarboxylic acid, 4,4'-diphenylmethanedicarboxylic acid and 3,3'-diphenylmethanedicarboxylic acid, 4,4'-sulfodiphenylcarboxylic acid and 3,3'-sulfodiphenylcarboxylic acid, 1,4-naphthalene dicarboxylic acid or 2,6-naphthalene dicarboxylic acid, phenoxyterephthalic acid, particularly preferably isophthalic acid.
[0078] Other polyamide-forming monomers A4) can be derived from dicarboxylic acids having 4 to 16 carbon atoms and aliphatic or cycloaliphatic diamines having 4 to 16 carbon atoms, and aminocarboxylic acids / corresponding lactams having 7 to 12 carbon atoms. Examples of suitable monomers of these types mentioned are suberic acid, azelaic acid and sebacic acid as representatives of aliphatic dicarboxylic acids; 1,4-butanediamine, 1,5-pentanediamine, piperazine, 4,4'-diaminodicyclohexylmethane, 2,2-(4,4'-diaminodicyclohexyl)propane and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane as representatives of diamines or m-xylylenediamine as representatives of diamines and caprolactam, enantholactam, w-aminoundecanoic acid and laurolactam as representatives of lactams / aminocarboxylic acids.
[0079] Suitable copolyamides of this type are described more particularly in DE-A-10 2009 011 668.
[0080] The following non-comprehensive list includes the above-mentioned polyamides and other suitable polyamides for the purposes of the present invention, and the monomers included:
[0081] AB polymer:
[0082]
[0083] AA / BB polymer:
[0084]
[0085]
[0086] AA / BB polymer:
[0087]
[0088] Preferred polyamides A and B are PA 6, PA 66, PA 6 / 66, PA 66 / 6, PA 12, PA 610, PA46, PA 6T / 6, PA 6T / 66, PA 9T, PA 10T, PA 6I / 6T, PA 6T / 6I, PA 6T / 6I / 66, PA 66 / 6T and PA4T, more preferably PA 6, PA 66, PA 6 / 66 or PA 66 / 6 and mixtures thereof.
[0089] Polyamide A is preferably a polyamide comprising polyamide from post-industrial (=pre-consumer) and / or post-consumer waste, preferably from an extrusion process selected from the group of blow molding, film extrusion, pipe extrusion, sheet extrusion, fiber spinning and mixtures thereof.
[0090] Preferred polymers A comprise sorted polyamide waste, ie comprise only polyamide as polymer component. The polyamide may be a mixture of 2 or more different polyamides or one polyamide. Suitable polyamides are as described above.
[0091] The preferred polyamide A comprising a polyamide from post-industrial (= pre-consumer) and / or post-consumer waste, preferably a polyamide from an extrusion process selected from the group of blow molding, film extrusion, tube extrusion, sheet extrusion, fiber spinning and mixtures thereof, can in one embodiment be used in the process according to the invention in combination with one or more residual filler materials and / or one or more residual additives present in the post-industrial (= pre-consumer) and / or post-consumer waste. Fillers and additives depend on the type of post-industrial (= pre-consumer) and / or post-consumer waste and are known to the person skilled in the art.
[0092] An advantage of the process of the present invention is that residual fillers and additives do not interfere with the process of the present invention.
[0093] However, the polyamide A used in the present invention is preferably used in the absence of significant amounts of residual filler materials and / or additives (i.e., preferably no more than 5 wt. % residual filler materials and no more than 1 wt. % residual additives are present, based on polyamide A), more preferably, polyamide A is used in the present method in the absence of residual filler materials and / or additives.
[0094] In one embodiment, polyamide A is a polyamide (Aa) consisting of 100% polyamide from post-industrial and / or post-consumer waste, preferably from an extrusion process selected from the group of blow molding, film extrusion, tube extrusion, sheet extrusion, fiber spinning and mixtures thereof or a mixture of:
[0095] Aa is derived from post-industrial and / or post-consumer waste, preferably a polyamide (Aa) from an extrusion process selected from the group consisting of blow molding, film extrusion, tube extrusion, sheet extrusion, fiber spinning and mixtures thereof, and
[0096] Ab virgin polyamide (Ab).
[0097] Preferably, the polyamide A thus comprises
[0098] Aa 50 wt% to 100 wt%, preferably 80 wt% to 100 wt%, more preferably
[0099] 90 to 100 wt.% of post-industrial and / or post-consumer waste, preferably from an extrusion process (Aa) selected from the group of blow molding, film extrusion, tube extrusion, sheet extrusion, fiber spinning and mixtures thereof, and
[0100] Ab 0 to 50 wt. %, preferably 0 to 20 wt. %, more preferably 0 to 10 wt. % of virgin polyamide (Ab),
[0101] The total amount of (Aa) and (Ab) is 100% by weight.
[0102] More preferably, polyamide A comprises
[0103] Aa 100 wt.-% post-industrial and / or post-consumer waste, preferably from an extrusion process (Aa) selected from the group of blow molding, film extrusion, tube extrusion, sheet extrusion, fiber spinning and mixtures thereof.
[0104] The polyamides A mentioned above are suitable as polyamides Aa and Ab.
[0105] The present invention can provide an injection molding PA (polyamide B) using 100% recycled extrusion grade PA (polyamide A).
[0106] In the meaning of this application, "waste" means any substance or object that is disposed of or intended to be disposed of or is required to be disposed of by the holder (EU legal definition).
[0107] In the meaning of the present application, pre-consumer (= post-industrial) waste originates from the production of a product, post-consumer waste originates from its use.
[0108] “Recycling” means any recovery operation in which waste is reprocessed into products, materials or substances, whether for its original purpose or for another purpose. Recycling includes the reprocessing of organic materials but does not include energy recovery and reprocessing into material for use as fuel or for backfill operations (Article 3(17) of the Waste Framework Directive (WFD)).
[0109] Post-industrial (=pre-consumer) and / or post-consumer waste polyamide used in the process according to the invention preferably originates from the extrusion industry, especially from the production of fibers, sheets, films, tubes and profiles by extrusion.
[0110] According to the present application, one object of the present invention is to recycle polyamide A, especially post-industrial and / or post-consumer polyamide scrap originating from the extrusion industry, to provide recycled polyamide B with good flowability and sufficient melt stability for injection molding applications.
[0111] Thus, polyamide B comprises the same class of polyamides as polyamide A, but has a lower viscosity than polyamide A. Suitable classes of polyamides are described above.
[0112] However, polyamides originating from post-industrial and / or post-consumer waste from the extrusion industry, which are preferably contained in polyamide A, have a viscosity that is too high to be reused in injection molding applications. Reusing such materials for injection molding applications requires reducing the melt viscosity of the recycled material.
[0113] The present invention therefore provides a method for reducing the viscosity of polyamide A, wherein the concentration ratio of the terminal groups (amino groups and carboxylic acid groups) of the starting polyamide A is preferably kept constant (deviation of about + / - 20%, preferably about + / - 10%). Thus, the melt stability (MVR over time) of the recycled polyamide B is ensured, which is a prerequisite for the use of recycled polymers, in particular in injection molding, preferably at low concentrations of additives.
[0114] The process of the invention for making polyamide B comprises melt mixing polyamide A with salts of diacids and diamines. Suitable polyamides A and B, suitable salts of diacids and diamines C and suitable amounts of the salts of diacids and diamines are mentioned above.
[0115] In the process of the invention, the melt mixing of polyamide A with the salt of diacid and diamine is optionally carried out in the presence of filler (D) and / or at least one further additive (E). In the presence of filler (D) and / or at least one further additive (E), a polymer composition for injection molding comprising recycled polymer B is obtained directly by the process of the invention without further processing steps. Suitable fillers (D) and further additives (E) are described below.
[0116] In said embodiment, polyamide A is preferably fed into an extruder and optionally compounded with at least one further additive (E) and / or filler material (D) to produce a polyamide grade for injection molding. The inventive addition of the salt of the diacid and diamine in the first stage of extrusion results in a rapid and uniform reduction in the molecular weight of the recycled material via transamidation. In order to effectively reduce the viscosity of polyamide A, only a small amount of the salt of the diacid and diamine is required (generally less than or equal to 1 wt%, preferably 0.01 wt% to 1 wt%, more preferably 0.1 wt% to 0.9 wt%, most preferably 0.15 wt% to 0.5 wt%).
[0117] Preferably, melt mixing is carried out in an extruder. The extruder can be a single screw, a twin screw or a multi-screw extruder. A twin screw extruder is preferred. A twin screw extruder is also referred to as a double screw extruder. A twin screw extruder can be co-rotating or counter-rotating. Single screw extruders, twin screw extruders and multi-screw extruders are known to those skilled in the art and are described, for example, in C. Rauwendaal: Polymer extrusion, Carl Hanser Verlag GmbH & Co. KG, 5th edition (January 16, 2014), pages 13-47.
[0118] The extruder may include additional devices, such as mixing elements or kneading elements. The mixing element is used to mix the individual components contained in the extruder. Suitable mixing elements are known to the skilled person and are, for example, static mixing elements or dynamic mixing elements. Kneading elements are also used to mix the individual components contained in the extruder. Suitable kneading elements are known to the skilled person and are, for example, kneading screws or kneading blocks, such as disc kneading blocks or shoulder kneading blocks.
[0119] The extruder is operated continuously or discontinuously, ie the process according to the invention is a continuous or discontinuous process.
[0120] In the melt mixing method of the present invention, the temperature of the extruder during melt mixing may be any temperature and is usually in the range of 200°C to 380°C, preferably in the range of 220°C to 350°C, and particularly preferably in the range of 240°C to 340°C.
[0121] The barrel temperature of the extruder may be higher than the temperature of the components in the extruder, and it is also possible that the barrel temperature of the extruder is lower than the temperature of the components in the extruder. For example, when the components are heated, the barrel temperature of the extruder may initially be higher than the temperature of the components in the extruder. When the components in the extruder are cooled, the barrel temperature of the extruder may be lower than the temperature of the components in the extruder. The temperature given in the present invention and related to the extruder means the barrel temperature of the extruder. "Barrel temperature of the extruder" means the temperature of the barrel of the extruder. Therefore, the barrel temperature of the extruder is the temperature of the outer wall of the extruder barrel. As an extruder, any extruder known to the technician that can be used at a temperature and pressure during compounding is suitable. Generally speaking, the extruder can be heated to a temperature at least to compound polyamide A, a salt of a diacid and a diamine and optionally at least one additional additive (E) and / or a filling material (D).
[0122] Polyamide A and the salt of diacid and diamine and optionally at least one additional additive (E) and / or filler (D) can be added to the extruder continuously or simultaneously and mixed and compounded in the extruder to obtain polyamide B or the polyamide composition described below. In a preferred embodiment, the salt C of diacid and diamine is added to polyamide A in a first step. In a second step, at least one additional additive (E) and / or filler (D) is optionally added. The diacid and diamine of the salt C are added to the extruder in the form of the salt C, or alternatively, the diacid and diamine are added separately and the salt C is formed in the extruder.
[0123] In the process according to the invention, polyamide A is melt-mixed with a salt of a diacid and a diamine. By said process, a polyamide B having a viscosity value lower than that of polyamide A is obtained. Strictly speaking, since the salt C of a diacid and a diamine is present together with polyamide A in the process according to the invention, a polyamide B is formed which comprises the same units selected from the combination of one or more diamines with one or more diacids, one or more lactams and mixtures thereof as polyamide A, and additionally units derived from the diacid and diamine forming the salt C. In the case where polyamide A comprises units based on the same diacid and diamine as those present in the salt C, said units cannot be distinguished, which is the case, for example, of polyamide 66 as polyamide A and the salt C of adipic acid and hexamethylenediamine. However, in the case where the units derived from the diacid and diamine forming the salt C in polymer B are different from the units forming polyamide A, a polymer B1 is obtained which comprises, in addition to the units already present in polymer A, a small amount of units derived from the diacid and diamine forming the salt C. Since the viscosity of the polymer formed from the same units already present in polymer A is different from the viscosity of polymer A, ie a polymer different from polymer A is formed, said polymer is referred to hereinafter as polymer B*.
[0124] The invention therefore further relates to a polyamide B1 consisting of:
[0125] a) 99.00 to 99.99 wt. %, preferably 99.10 to 99.90 wt. %, more preferably 99.50 to 99.85 wt. % of a polyamide B* formed from units selected from the group consisting of one or more diamines in combination with one or more diacids, one or more lactams and mixtures thereof, and
[0126] b) 0.01 to 1% by weight, preferably 0.1 to 0.9% by weight, more preferably 0.15 to 0.5% by weight, of units derived from diacids and diamines forming the salt C,
[0127] wherein the units derived from the diacid and the diamine forming the salt C are different from the units forming the polyamide B*.
[0128] Preferred salts C are as described above. More preferably, the diacid and diamine forming salt C are adipic acid and hexamethylenediamine.
[0129] Polyamide B* comprises the same units as polyamide A, said units being selected from the combination of one or more diamines with one or more diacids, one or more lactams and mixtures thereof. Suitable units selected from the combination of one or more diamines with one or more diacids, one or more lactams and mixtures thereof are mentioned above to form polyamide A and thus polyamide B*.
[0130] The ratio of the amino end group concentration of polyamide B1 to the carboxyl end group concentration of polyamide B is preferably ≥ 0.2, more preferably ≥ 0.40, most preferably ≥ 0.70.
[0131] Polyamide B1 is a subgroup of polyamide B. The only difference between polyamide B and polyamide B1 is that the units derived from the diacid and the diamine forming the salt C are different from the units derived from polyamide A (these units correspond to the units forming polyamide B*).
[0132] That is, polyamide B consists of:
[0133] a) 99.00 to 99.99 wt. %, preferably 99.10 to 99.90 wt. %, more preferably 99.50 to 99.85 wt. % of a polyamide B* formed from units selected from the group consisting of one or more diamines in combination with one or more diacids, one or more lactams and mixtures thereof, and
[0134] b) 0.01 to 1% by weight, preferably 0.1 to 0.9% by weight, more preferably 0.15 to 0.5% by weight, of units derived from diacids and diamines forming the salt C.
[0135] The invention therefore further relates to a polyamide B1 consisting of:
[0136] a) 99.00% to 99.99% by weight, preferably 99.10% to 99.90% by weight, more preferably 99.50% to 99.85% by weight of PA 6, and
[0137] b) 0.01 to 1% by weight, preferably 0.1 to 0.9% by weight, more preferably 0.15 to 0.5% by weight, of units derived from the salt C of adipic acid and hexamethylenediamine.
[0138] In a further embodiment the invention relates to polyamide B obtained by the process according to the invention, wherein the ratio of the amino end group concentration of polyamide B to the carboxyl end group concentration of polyamide B is preferably ≥ 0.2, more preferably ≥ 0.40, most preferably ≥ 0.70.
[0139] The determination of the amino end group concentration and the carboxyl end group concentration is as described above. Furthermore, suitable polyamides B are as described above.
[0140] The microstructure of polyamide B1 is different from the microstructure of polyamides obtained by a polymerization process in which monomers forming the polyamide (e.g., caprolactam monomers) are polymerized in the presence of a salt of a diacid and a diamine (e.g., an equimolar salt of hexamethylenediamine and adipic acid), as disclosed, for example, in JP 2001 200054A, JP H09 234789A, and WO 2018 / 165641 A1.
[0141] As described in WO 2018 / 165641 A1, when caprolactam monomers are polymerized in the presence of an equimolar salt of hexamethylenediamine and adipic acid, polyamide 6 / 66 copolymers formed from substantially randomly distributed caprolactam monomers and hexamethylenediamine monomers are formed (see, for example, paragraph
[0026] in WO 2018 / 165641 A1).
[0142] However, the polyamide B1 according to the invention is composed of a polyamide B*, which in the most preferred embodiment may be a polyamide 6, and 0.01 to 1% by weight of units derived from a diacid and a diamine, preferably a salt of adipic acid and hexamethylenediamine, which form a salt C. Thus, the polyamide B1 does not form a polyamide 6 / 66 copolymer in which the caprolactam-based units and the hexamethylenediamine-based units are randomly distributed.
[0143] Without being bound by theory, it is expected that in the process of the present invention, a dimer or oligomer is first formed from the salt C and then incorporated into the polymer chain B* by an exchange reaction with the polymer B*. In polyamide B1, the monomer units forming the polymer B* and the monomer units based on the salt C are not randomly distributed, but the polyamide B1 contains terminal groups formed by the salt C and blocks formed by the dimer or oligomer formed by the salt C.
[0144] Therefore, the microstructure of polyamide B1 is different from the microstructure of polyamides disclosed, for example, in JP 2001 200054A, JP H09234789A and WO 2018 / 165641 A1.
[0145] The present invention further relates to a polyamide composition comprising:
[0146] (i) a polyamide B1 or a polyamide B according to the invention; and
[0147] (ii) optionally a filler material (D) and
[0148] (iii) optionally at least one further additive (E);
[0149] At least one filler material (D) or another additive is present therein.
[0150] Preferably, the polyamide composition comprises:
[0151] (i) 40% to 99.9% by weight, preferably 50% to 99.75% by weight, more preferably 60% to 99.5% by weight of polyamide B1 or polyamide B according to the invention; and
[0152] and
[0153] (ii) contains 0 to 60 wt %, preferably 0 to 50 wt %, more preferably 0 to 40 wt % of filler (D), and
[0154] (iii) 0 wt% to 25 wt%, preferably 0 wt% to 20 wt%, more preferably 0 wt%
[0155] to 15% by weight of at least one further additive (E),
[0156] wherein at least one filler material (D) or one further additive (E) is present,
[0157] in
[0158] Where filler material (D) is used, the minimum amount is preferably 10 wt%, more preferably 15 wt%, most preferably 20 wt%; and
[0159] In case further additives (E) are used, the minimum amount is preferably 0.1 wt. %, more preferably 0.25 wt. %, most preferably 0.5 wt. %,
[0160] The total amount of components B1 or B, D and E is 100% by weight.
[0161] Polyamide B1 and polyamide B are as described above.
[0162] The filling material (D) may include one or more of the following fillers.
[0163] As component D, the polyamide composition comprises 0% to 60% by weight, preferably 0% to 50% by weight, more preferably 0% to 40% by weight, of at least one filler material, which is generally a fibrous and / or particulate filler.
[0164] Preferably, component D comprises glass fibers and is present in an amount of 10 to 60 wt%, more preferably 15 to 50 wt%, most preferably 20 to 40 wt%.
[0165] If component D is present, the maximum amount of polyamide B1 or polyamide B is reduced by the minimum amount of component D, so that the total amount of components B1 or B, D and E is still 100% by weight.
[0166] Fibrous or particulate fillers D which may be mentioned are carbon fibers, glass fibers, glass beads, amorphous silica, calcium silicate, calcium metasilicate, magnesium carbonate, kaolin, chalk, powdered quartz, mica, barium sulfate and feldspar.
[0167] Preferred fibrous fillers which may be mentioned are carbon fibers, aramid fibers and potassium titanate fibers, particular preference being given to glass fibers in the form of E glass. These can be used as rovings or in the form of commercially available chopped glass.
[0168] The fiber filler may be surface pretreated with a silane compound to improve compatibility with the thermoplastic material.
[0169] Suitable silane compounds have the following general formula:
[0170] (X-(CH2) n ) k -Si-(OC m H 2m+1 ) 4-k
[0171] The substituents are defined as follows:
[0172]
[0173] n is an integer from 2 to 10, preferably from 3 to 4,
[0174] m is an integer of 1 to 5, preferably 1 to 2, and
[0175] k is an integer of 1 to 3, preferably 1.
[0176] Preferred silane compounds are aminopropyltrimethoxysilane, aminobutyltrimethoxysilane, aminopropyltriethoxysilane and aminobutyltriethoxysilane, and the corresponding silanes which contain a glycidyl group as substituent X.
[0177] The amount of silane compounds generally used for surface coating is 0.01% to 2% by weight, preferably 0.025% to 1.0% by weight and in particular 0.05% to 0.5% by weight (based on component D).
[0178] Acicular mineral fillers are also suitable.
[0179] For the purposes of the present invention, needle-shaped mineral fillers are mineral fillers with strongly developed needle-shaped features. An example is needle-shaped wollastonite. The mineral preferably has an L / D (length to diameter) ratio of 8:1 to 35:1, preferably 8:1 to 11:1. The mineral filler can optionally be pretreated with the above-mentioned silane compounds, but pretreatment is not necessary.
[0180] Other fillers that can be mentioned are kaolin, calcined kaolin, wollastonite, talc and chalk, and lamellar or needle-shaped nano fillers, and the amount of these fillers is preferably 0.1 to 10%. The material that is preferably used for this purpose is boehmite, bentonite, montmorillonite, vermiculite, hectorite and synthetic hectorite. The lamellar nano filler is organically modified by the method of the prior art so that it has good compatibility with the organic binder. Adding lamellar or needle-shaped nano fillers to the nanocomposite material of the present invention further improves mechanical strength.
[0181] As component E, the polyamide composition of the invention may contain 0% to 25% by weight, preferably 0% to 20% by weight, more preferably 0% to 15% by weight, of at least one further additive.
[0182] If component E is present, the maximum amount of polyamide B1 or polyamide B is reduced by the minimum amount of component E, so that the total amount of components B1 or B, D and E is still 100% by weight.
[0183] If at least one further additive is used, the minimum amount is preferably 0.1 wt.-%, more preferably 0.25 wt.-%, most preferably 0.5 wt.-%.
[0184] The polyamide composition of the present invention may contain as component E conventional processing aids, other stabilizers, oxidation retarders, agents for resisting thermal and UV decomposition, lubricants and mold release agents, colorants such as dyes and pigments, nucleating agents, plasticizers, and the like.
[0185] The polyamide composition of the invention may comprise, as component E1, 0.05% to 3% by weight, preferably 0.1% to 1.5% by weight, in particular 0.1% to 1% by weight, of a lubricant.
[0186] Preference is given to salts of Al, alkali metals or alkaline earth metals, or esters or amides of fatty acids having 10 to 44 carbon atoms, preferably 12 to 44 carbon atoms.
[0187] The metal ions are preferably alkaline earth metals and Al, particularly preferably Ca or Mg.
[0188] Preferred metal salts are calcium stearate and calcium montanate, and aluminum stearate.
[0189] It is also possible to use mixtures of the various salts in any desired mixing ratios.
[0190] The carboxylic acids may be monobasic or dibasic. Examples which may be mentioned are pelargonic acid, palmitic acid, lauric acid, heptadecanoic acid, dodecanedioic acid, behenic acid, and particular preference is given to stearic acid, capric acid and montanic acid (a mixture of fatty acids having 30 to 40 carbon atoms).
[0191] The fatty alcohols may be monohydric to tetrahydric. Examples of alcohols are n-butanol, n-octanol, stearyl alcohol, ethylene glycol, propylene glycol, neopentyl glycol, pentaerythritol, preferably glycerol and pentaerythritol.
[0192] The aliphatic amines may be monobasic or tribasic. Examples of these aliphatic amines are stearylamine, ethylenediamine, propylenediamine, hexamethylenediamine, di(6-aminohexyl)amine, ethylenediamine and hexamethylenediamine being particularly preferred. Preferred esters or amides are, respectively, glyceryl distearate, glyceryl tristearate, ethylenediamine distearate, glyceryl monopalmitate, glyceryl trilaurate, glyceryl monobehenate and pentaerythritol tetrastearate.
[0193] It is also possible to use mixtures of various esters or amides, or combinations of esters and amides in any desired mixing ratio.
[0194] As component E, the polyamide composition according to the invention can comprise preferably 0.01 to 3% by weight, particularly preferably 0.02 to 2% by weight and in particular 0.05 to 1.0% by weight, based on the total weight of the composition, of at least one heat stabilizer.
[0195] The heat stabilizer is preferably selected from the group consisting of copper compounds, aromatic secondary amines, hindered phenols, phosphites, phosphonites, and mixtures thereof.
[0196] As component E, it is possible to use 0.05 to 3% by weight, preferably 0.1 to 2% by weight and in particular 0.1 to 1% by weight of at least one hindered phenol antioxidant.
[0197] This component E preferably has a molecular weight of greater than 500 g / mol, more preferably greater than 1000 g / mol. In addition, component C should preferably show a high thermal stability, for example a maximum of 5% weight loss, more preferably a maximum of 2% weight loss, measured in a TGA (thermogravimetric analysis) experiment at 300° C. under nitrogen (from 40° C. to 120° C. at 10° C. / min, isothermal at the latter temperature for 15 minutes, then from 120° C. to 600° C. at 20° C. / min).
[0198] Component E preferably has at least one, more preferably at least two, branched chains C 3-12 The phenolic group substituted with an alkyl group acts as a steric hindering group. The substituted phenolic group is covalently linked to the structure of component E.
[0199] Suitable sterically hindered phenols E are in principle all compounds which have a phenolic structure and which have at least one bulky group on the phenolic ring. 3-12 -alkyl group, preferably branched C 3-6 - an alkyl group, more preferably an isopropyl or tert-butyl group.
[0200] Preferably, compounds of the formula:
[0201]
[0202] in:
[0203] R 1 and R 2 is an alkyl group, a substituted alkyl group or a substituted triazole group, and wherein the group R 1 and R 2 can be the same or different, and R 3 is an alkyl group, a substituted alkyl group, an alkoxy group or a substituted amino group. The alkyl and alkoxy residues preferably have 1 to 12 carbon atoms, more preferably 1 to 6 carbon atoms. The substituents are preferably C 1-12 -alkyl, more preferably C 1-6 -alkyl, most preferably C 1-4 -alkyl. 1 To R 3 At least one of is preferably a bulky group as defined above.
[0204] Antioxidants of the aforementioned type are described, for example, in DE-A 27 02 661 (US Pat. No. 4,360,617).
[0205] Another group of preferred hindered phenols is provided by those radicals derived from substituted phenylcarboxylic acids, in particular derived from substituted phenylpropionic acids, said radicals preferably having at least one bulky group on the phenyl group. Said radicals contain in their structure at least one, preferably two, covalently linked substituted phenylcarboxylic acid units, which preferably have at least one bulky group on the phenyl group.
[0206] The preferred phenyl carboxylic acid is phenyl-C 1-12 -carboxylic acid, more preferably phenyl-C 2-6 As mentioned above, the phenyl group is preferably a phenol group having at least one bulky group on the phenol ring. Therefore, the above-mentioned hindered phenol is preferably 1-12 -alkanecarboxylic acid, more preferably straight chain C 2-6 -Alkane carboxylic acid is covalently linked.
[0207] Particularly preferred compounds of this type are those of the formula
[0208]
[0209] Where R 4 , R 5 , R 7 and R 8 are independently C1-C8-alkyl groups, which themselves may have substituents (at least one of these groups is a bulky group), and R 6 R is a divalent aliphatic group having 1 to 10 carbon atoms and whose main chain may further have a CO bond. 4 To R 8 At least one of is a bulky group as defined above.
[0210] Preferred compounds corresponding to these formulae are
[0211]
[0212] ( 245, from BASF SE)
[0213]
[0214] ( 259, from BASF SE)
[0215] As examples of hindered phenols, all of the following should be mentioned:
[0216] 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]( 1010 from BASF SE), distearyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate, 2,6,7-trioxa-1-phosphabicyclo[2.2.2]octan-4-ylmethyl 3,5-di-tert-butyl-4-hydroxyhydrocinnamate, 3,5-di-tert-butyl-4-hydroxyphenyl-3,5-distearylthiotriazolylamine, 2-(2'-hydroxy-3'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2,6-di-tert-butyl-4-hydroxymethylphenol, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-benzene, 4,4'-methylenebis(2,6-di-tert-butylphenol), 3,5-di-tert-butyl-4-hydroxybenzyldimethylamine.
[0217] Compounds which have proven to be particularly effective and which are therefore preferably used are 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 1,6-hexanediol bis(3,5-di-tert-butyl-4-hydroxyphenyl) propionate ( 259), pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and N,N'-hexamethylenebis-3,5-di-tert-butyl-4-hydroxyhydrocinnamamide ( 1098) and the above-mentioned products from BASF SE 245 and 1010, they have particularly good applicability.
[0218] In certain cases, sterically hindered phenols having not more than one sterically hindering group in the ortho position relative to the phenolic hydroxyl group have proven to be particularly advantageous; in particular when assessing color fastness during storage over a long period of time in diffuse light.
[0219] Furthermore, it is advantageous to use sterically hindered phenolic antioxidants which also have a sufficiently high molecular weight, preferably a molecular weight of more than 500 g / mol, in particular more than 1000 g / mol. Furthermore, they preferably exhibit a high thermal stability measured by TGA (thermogravimetric analysis), with a degradation of less than 2% up to 300° C. under a nitrogen atmosphere.
[0220] The polyamide composition of the invention may comprise, as component E2, 0.05 to 3% by weight, preferably 0.1 to 1.5% by weight, and in particular 0.1 to 1% by weight of a copper stabilizer, preferably a Cu(I) halide, in particular as a mixture with an alkali metal halide, preferably KI, in particular in a ratio of 1:4, or a hindered phenol, or a mixture thereof.
[0221] Preferred monovalent copper salts used are cuprous acetate, cuprous chloride, cuprous bromide and cuprous iodide. The material contains these in an amount of 5 ppm to 500 ppm of copper, preferably 10 ppm to 250 ppm, based on the polyamide.
[0222] Advantageous properties are particularly obtained if the copper is present in the polyamide in molecular distribution. This can be achieved if a concentrate comprising polyamide, comprising a monovalent copper salt and comprising an alkali metal halide is added to the molding composition in the form of a solid, homogeneous solution. For example, a typical concentrate consists of 79% to 95% by weight of polyamide and 21% to 5% by weight of a mixture consisting of cuprous iodide or cuprous bromide and potassium iodide. The copper concentration in the solid homogeneous solution is preferably 0.3% to 3% by weight, in particular 0.5% to 2% by weight, based on the total weight of the solution, and the molar ratio of cuprous iodide to potassium iodide is 1 to 11.5, preferably 1 to 5.
[0223] Suitable polyamides for the concentrate are homopolyamides and copolyamides, in particular PA 6.
[0224] According to a preferred embodiment of the invention, the molding composition is free of copper, in particular free of copper stabilizers such as Cu / (I) halides, and combinations of Cu(I) halides with alkali metal halides.
[0225] More preferably, the thermoplastic molding composition of the invention is free of metal halides.Systems free of metal halides, so-called electro-friendly systems, are of great interest since electromobility, electrification and connectivity are a growing trend in almost all industries.
[0226] Therefore, the polyamide composition is preferably free of metal halides, in particular Cu halides and alkali metal halides.
[0227] The polyamide composition of the invention may contain 0.001% to 10% by weight, preferably 0.05% to 5% by weight, in particular 0.1% to 2.5% by weight of particles having a particle size of up to 10 μm (d 50 The iron powder may preferably be obtained by thermal decomposition of pentacarbonyl iron.
[0228] Iron exists in several allotropes:
[0229] 1. α-Fe (ferrite) forms a cubic lattice with a space center, is magnetizable, dissolves a small amount of carbon, and occurs in pure iron up to 928°C. At 770°C (Curie temperature), it loses its ferromagnetism and becomes paramagnetic; iron in the temperature range of 770°C to 928°C is also called β-Fe. At room temperature and a pressure of at least 13 000 MPa, α-Fe becomes known as ε-Fe, with a volume reduction of about 0.20 cm 3 / mol, so the density increases from 7.85 to 9.1 (at 20 000MPa);
[0230] 2. γ-Fe (austenite) forms a face-centered cubic lattice, is non-magnetic, dissolves a large amount of carbon, and is only observed in the temperature range of 928°C to 1398°C;
[0231] 3. Delta-Fe, centered in space, exists at a melting point of 1398°C to 1539°C.
[0232] Metallic iron is usually silvery white, with a density of 7.874 (heavy metal), a melting point of 1539°C, a boiling point of 2880°C, and a specific heat (from 18°C to 100°C) of about 0.5g. -1 K -1 , tensile strength is 220N / mm 2 Up to 280N / mm 2. These values apply to chemically pure iron.
[0233] The industrial production of iron uses the smelting of iron ore, slag, calcined pyrite or blast furnace dust, and the remelting of scrap and alloys.
[0234] The iron powder of the invention is prepared via thermal decomposition of iron pentacarbonyl, preferably at a temperature of 150 to 350° C. The particles thus obtainable preferably have a spherical shape, thus being spherical or almost spherical (another term used is spherulite).
[0235] Preferred iron powders have the particle size distribution described below; the particle size distribution is determined here by laser scattering in very dilute aqueous suspension (eg using Beckmann LS 13320). The particle sizes (and distributions) described below can optionally be obtained via grinding and / or sieving.
[0236] Here d xx It means that XX% of the total volume of particles is less than the specified value.
[0237] d 50 Value: up to 10 μm, preferably 1.6 μm to 8 μm, in particular 2.9 μm to 7.5 μm, very particularly 3.4 μm to 5.2 μm
[0238] d 10 Value: preferably 1 μm to 5 μm, in particular 1 μm to 3 μm, and very particularly 1.4 μm to 2.7 μm
[0239] d 90 Values: preferably 3 μm to 35 μm, in particular 3 μm to 12 μm and very particularly 6.4 μm to 9.2 μm.
[0240] The iron powder preferably has an iron content of 97 g / 100 g to 99.8 g / 100 g, preferably 97.5 g / 100 g to 99.6 g / 100 g. The content of other metals is preferably below 1000 ppm, in particular below 100 ppm and very particularly below 10 ppm.
[0241] The Fe content is usually determined by infrared spectroscopy.
[0242] The carbon content is preferably 0.01 g / 100 g to 1.2 g / 100 g, preferably 0.05 g / 100 g to 1.1 g / 100 g, and in particular 0.4 g / 100 g to 1.1 g / 100 g. This carbon content in the preferred iron powder corresponds to the carbon content of the powder after the thermal decomposition process without hydrogen reduction.
[0243] The carbon content is usually determined by burning the sample in an oxygen stream and then detecting the resulting CO 2 gas using IR by a method based on ASTM E1019 (by means of Leco CS230 or CS-mat 6250 from Juwe).
[0244] The nitrogen content is preferably at most 1.5 g / 100 g, preferably 0.01 g / 100 g to 1.2 g / 100 g.
[0245] The oxygen content is preferably at most 1.3 g / 100 g, preferably 0.3 g / 100 g to 0.65 g / 100 g.
[0246] N and O are determined by heating the sample to about 2100° C. in a graphite furnace. The oxygen obtained from the sample is converted into CO here and measured by an IR detector. The N released from the N-containing compound under the reaction conditions is discharged with the carrier gas and detected and recorded by a TCD (thermal conductivity detector) (both methods are based on ASTM E1019).
[0247] The tap density is preferably 2.5 g / cm 3 Up to 5g / cm 3 , especially 2.7g / cm 3 Up to 4.4g / cm 3 This generally refers to the density when the powder is, for example, filled into a container and compacted by vibration. Further preferred iron powders may be surface-coated with iron phosphate, iron phosphite or SiO2.
[0248] The BET surface area according to DIN ISO 9277 is preferably 0.1 m 2 / g to 10m 2 / g, especially 0.1m 2 / g to 5m 2 / g, and preferably 0.2m 2 / g to 1m 2 / g, and especially 0.4m 2 / g to 1m 2 / g.
[0249] In order to achieve a particularly good dispersion of the iron particles, a masterbatch comprising a polymer can be used. Suitable polymers for this purpose are polyolefins, polyesters or polyamides, and it is preferred here that the masterbatch polymer is identical to component A. The mass fraction of iron in the polymer is generally 15% to 80% by weight, preferably 20% to 40% by weight.
[0250] UV stabilizers which may be mentioned are various substituted resorcinols, salicylates, benzotriazoles and benzophenones, generally in amounts of up to 2% by weight, based on the polyamide composition. Nigrosine may also be used.
[0251] Materials that may be added as colorants are inorganic pigments such as titanium dioxide, ultramarine blue, iron oxide and carbon black, and organic pigments such as phthalocyanine, quinacridone, perylene, and dyes such as anthraquinone.
[0252] Materials that can be added as colorants are inorganic pigments such as titanium dioxide, ultramarine blue, iron oxide, and carbon black; and organic pigments such as phthalocyanine, quinacridone, perylene; and dyes such as anthraquinone.
[0253] Materials that can be used as nucleating agents are sodium phenylphosphinate, alumina, silica, and preferably talc.
[0254] The polyamide composition may also contain, as component E, flame retardants.
[0255] As component E, the polyamide composition can comprise 1.0% to 10.0% by weight, preferably 2.0% to 6.0% by weight, in particular 3.0% to 5.0% by weight, of at least one phosphazene of the general formula (IX) or (X) as flame retardant.
[0256] The minimum amount of component E (flame retardant) is at least 1.0% by weight, preferably 2.0% by weight, in particular 3.0% by weight.
[0257] The maximum amount of component E (flame retardant) is 10.0% by weight, preferably 6.0% by weight and particularly preferably 5.0% by weight.
[0258] "Phosphazene" is understood to mean a cyclic phosphazene of the general formula (IX)
[0259]
[0260] wherein m is an integer from 3 to 25, and R 4 and R 4’ Same or different and represents C1-C 20 -alkyl-, C6-C 30 -Aryl-, C6-C 30 -Arylalkyl or C6-C 30 -alkyl-substituted aryl or a linear phosphazene of formula (X)
[0261]
[0262] wherein n represents 3 to 1000 and X represents -N=P(OPh)3 or -N=P(O)OPh, and Y represents -P(OPh)4 or -P(O)(OPh)2.
[0263] The preparation of such phosphazenes is described in EP-A 0 945 478.
[0264] Particularly preferred is the formula (XI) P3N3C 36 Cyclic phenoxyphosphazene
[0265]
[0266] or a linear phenoxyphosphazene according to formula (XII)
[0267]
[0268] The phenyl group may be optionally substituted.Phosphazenes in the context of the present application are described in Mark, JE, Allcock, HR, West, R., Inorganic Polymers, Prentice Hall, 1992, pages 61 to 141.
[0269] Preferred as component E are cyclic phenoxyphosphazenes having at least three phenoxyphosphazene units. For example, the corresponding phenoxyphosphazenes are described in paragraphs
[0051] to
[0053] of US2010 / 0261818. Specific reference may be made to formula (I) therein. The corresponding cyclic phenoxyphosphazenes are further described in EP-A-2 100 919, in particular in paragraphs
[0034] to
[0038] thereof. The preparation can be carried out as described in paragraph
[0041] of EP-A-2 100 919. In one embodiment of the invention, the phenyl groups in the cyclic phenoxyphosphazene may be C 1-4 -Alkyl substitution is preferred when pure phenyl groups are involved.
[0270] For further description of cyclic phosphazenes, please refer to Chemie Lexikon, 9th edition, keyword "phosphazene". The preparation is carried out, for example, via cyclophosphazenes obtainable from PCl5 and NH4Cl, in which the chlorine groups in the cyclophosphazenes have been replaced by phenoxy groups by reaction with phenol.
[0271] Cyclic phenoxyphosphazene compounds can be prepared, for example, as described in Allcock, HR, Phosphorus-Nitrogen Compounds (Academic Press, 1972) and Mark, JE, Allcock, HR, West, R., Inorganic Polymers (Prentice Hall, 1992).
[0272] Component E is preferably a mixture of cyclic phenoxyphosphazenes having three and four phenoxyphosphazene units. The weight ratio of rings comprising three phenoxyphosphazene units to rings comprising four phenoxyphosphazene units is preferably about 80:20. Larger rings of phenoxyphosphazene units may also be present, but in smaller amounts. Suitable cyclic phenoxyphosphazenes are available from Fushimi Pharmaceutical Co., Ltd. under the name FP-100 was obtained. This was a matt white / yellowish solid with a melting point of 110° C., a phosphorus content of 13.4% and a nitrogen content of 6.0%. The proportion of rings containing three phenoxyphosphazene units was at least 80.0% by weight.
[0273] The polyamide composition may preferably comprise 1.0 to 6.0% by weight, preferably 2.5 to 5.5% by weight, in particular 3.0 to 5.0% by weight, of at least one aliphatic or aromatic ester of phosphoric acid or polyphosphoric acid as flame retardant.
[0274] For this reason, solid, non-migrating phosphoric acid esters with a melting point between 70° C. and 150° C. are particularly preferred. This results in a product that is easy to meter and exhibits significantly less migration in the molding material. Particularly preferred examples are the commercially available phosphoric acid ester PX-200 (CAS: 139189-30-3) from Daihachi, or Sol-DP from ICL-IP. Other phosphoric acid esters with appropriate phenyl group substitutions are possible when this allows the preferred melting range to be achieved. Depending on the substitution pattern in the ortho or para position on the aromatic ring, the general structural formula is as follows:
[0275]
[0276]
[0277] in
[0278] R 1 =H, methyl, ethyl or isopropyl, but H is preferred.
[0279] n=0 to 7, but preferably 0.
[0280] R 2-6 =H, methyl, ethyl or isopropyl, but preferably methyl. 6 Preferred with R 4 and R 5 same.
[0281] m=can be, but needs to be different, and is between 1, 2, 3, 4 and 5, but preferably 2.
[0282] R ″ = can be H, methyl, ethyl or cyclopropyl, but methyl and H are preferred.
[0283] Taking the PX-200 as a specific example:
[0284]
[0285] It is particularly preferred when at least one aromatic ester of polyphosphoric acid is used. Such aromatic polyphosphates are available, for example, from Daihachi Chemical under the name PX-200.
[0286] As component E, the polyamide composition according to the invention can comprise 5.0 to 30.0 wt. %, preferably 10.0 to 25.0 wt. %, in particular 12.0 to 20.0 wt. %, for example about 16.0 wt. % of at least one metal phosphinate or phosphinate as described below as flame retardant.
[0287] Examples of preferred flame retardants of component E are metal phosphinates derived from hypophosphorous acid. For example, metal salts of hypophosphorous acid with Mg, Ca, Al or Zn as metal can be used. Particularly preferred here is aluminum hypophosphite.
[0288] Also suitable are phosphinic acid salts of the formula (I) and / or diphosphinic acid salts of the formula (II) or polymers thereof.
[0289]
[0290] in
[0291] R 1 , R 2 are identical or different and represent hydrogen, linear or branched C1-C6-alkyl and / or aryl;
[0292] R 3 Indicates a straight or branched C1-C 10 -alkylene, C6-C 10 -arylene, -alkylarylene or -arylalkylene;
[0293] M represents Mg, Ca, Al, Sb, Sn, Ge, Ti, Zn, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K and / or a protonated nitrogen base;
[0294] m=1 to 4; n=1 to 4; x=1 to 4, preferably m=3, x=3.
[0295] Preferably, R 1 , R 2 are the same or different and represent hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl and / or phenyl.
[0296] Preferably, R3 represents a methylene group, an ethylene group, an n-propylene group, an isopropylene group, an n-butylene group, a tert-butylene group, an n-pentylene group, an n-octylene group or an n-dodecylene group, a phenylene group or a naphthylene group; a methylphenylene group, an ethylphenylene group, a tert-butylphenylene group, a methylnaphthylene group, an ethylnaphthylene group or a tert-butylnaphthylene group; a phenylmethylene group, a phenylethylene group, a phenylpropylene group or a phenylbutylene group.
[0297] Particularly preferably, R 1 , R 2 is hydrogen, methyl, ethyl, and M is Al, particularly preferably aluminum hypophosphite.
[0298] The production of the phosphinate is preferably carried out by precipitation of the corresponding metal salt from an aqueous solution. However, the phosphinate can also be precipitated in the presence of suitable inorganic metal oxides or sulfides (white pigments, such as TiO2, SnO2, ZnO, ZnS, SiO2) as support materials. This thus provides surface-modified pigments which can be used as laser-markable flame retardants for thermoplastic polyesters.
[0299] It is preferred when using metal salts of substituted phosphinic acids in which, compared to hypophosphorous acid, one or two hydrogen atoms have been replaced by phenyl, methyl, ethyl, propyl, isobutyl, isooctyl, or the group R'-CH-OH has been replaced by R'-hydrogen, phenyl, tolyl. The metal is preferably Mg, Ca, Al, Zn, Ti, Fe. Diethylaluminum phosphinate (DEPAL) is particularly preferred.
[0300] With regard to the description of phosphinates or diphosphinates, reference is made to DE-A 199 60 671 as well as DE-A 44 30 932 and DE-A 199 33 901.
[0301] Further flame retardants are, for example, halogen-containing flame retardants.
[0302] Suitable halogen-containing flame retardants are preferably brominated compounds, such as brominated diphenyl ether, brominated trimethylphenylindane (FR 1808 from DSB), tetrabromobisphenol A and hexabromocyclododecane.
[0303] Suitable flame retardants are preferably brominated compounds, such as brominated oligocarbonates (BC52 or BC 58 from Great Lakes), which have the following structural formula:
[0304]
[0305] Particularly suitable are polypentabromobenzyl acrylates where n>4 (eg FR 1025 from ICL-IP) having the formula:
[0306]
[0307] Preferred brominated compounds also include oligomeric reaction products of tetrabromobisphenol A with epoxides (n>3) (eg, FR 2300 and 2400 from DSB), which have the formula:
[0308]
[0309] The brominated oligostyrenes preferably used as flame retardants have an average degree of polymerization (number average) of 3 to 90, preferably 5 to 60, measured by vapor pressure osmometry in toluene. Cyclic oligomers are also suitable. In a preferred embodiment of the invention, the brominated oligostyrenes have the formula I shown below, in which R represents hydrogen or an aliphatic group, in particular an alkyl group, such as CH2 or C2H5, and n represents the number of repeating chain structural units. R 1 It can be H or bromine or a fragment of a conventional free radical former:
[0310]
[0311] The value n can be from 1 to 88, preferably from 3 to 58. The brominated oligostyrene contains 40.0% to 80.0% by weight, preferably 55.0% to 70.0% by weight of bromine. Preferred are products consisting mainly of polydibromostyrene. These substances can be melted without decomposition and are soluble in, for example, tetrahydrofuran. The substance can be prepared by ring bromination (optionally aliphatic hydrogenation) of styrene oligomers, which are obtained, for example, by thermal polymerization of styrene (according to DT-OS25 37385) or by free radical oligomerization of suitable brominated styrene. The production of flame retardants can also be achieved by ionic oligomerization of styrene and subsequent bromination. The amount of brominated oligostyrene necessary to impart flame retardant properties to polyamides depends on the bromine content. The bromine content in the molding material according to the present invention is from 2.0% to 30.0% by weight, preferably from 5.0% to 12.0% by weight.
[0312] The brominated polystyrene according to the invention is generally obtained by the process described in EP-A 047 549:
[0313]
[0314] The brominated polystyrenes obtainable by this process and commercially available are predominantly ring-substituted tribrominated products. n' (see III) generally has a value of 125 to 1500, which corresponds to a molecular weight of 42500 to 235000, preferably 130000 to 135000.
[0315] The bromine content (based on the content of ring-substituted bromine) is generally at least 50.0% by weight, preferably at least 60.0% by weight and in particular 65.0% by weight.
[0316] Commercially available powdered products generally have a glass transition temperature of 160° C. to 200° C. and are available, for example, from Albemarle under the name HP-7010 was obtained from Ferro Corporation under the name PB 68 obtained.
[0317] Mixtures of brominated oligostyrenes with brominated polystyrenes can also be used in the molding materials according to the invention, the mixing ratio being freely selectable.
[0318] Chlorine-containing flame retardants are also suitable, preferably Decoran from OxyChem
[0319] Suitable halogen-containing flame retardants are preferably ring-brominated polystyrene, brominated polybenzyl acrylate, brominated bisphenol A epoxide oligomer or brominated bisphenol A polycarbonate.
[0320] In one embodiment of the present invention, no halogen-containing flame retardants are used in the polyamide compositions according to the invention.
[0321] In the context of the present invention, a flame retardant melamine compound suitable as component E is a melamine compound which, when added to glass-fiber-filled polyamide molding materials, reduces the flammability and influences the burning behavior in a flame-retardant manner, leading to improved performance in the UL 94 test and the glow-wire test.
[0322] The melamine compound is for example selected from melamine borate, melamine phosphate, melamine sulfate, melamine pyrophosphate, melam, melem, cyanuramide or melamine cyanurate or mixtures thereof.
[0323] Melamine cyanurates which are preferably suitable according to the invention are reaction products of melamine (formula I) and cyanuric acid / isocyanuric acid (formulas Ia and Ib) in preferably equimolar amounts.
[0324]
[0325] It is obtained, for example, by reacting an aqueous solution of the starting compounds at 90° C. to 100° C. Commercially available products are 50 1.5 to 7 μm and d 99 White powder with a particle size of less than 50 μm.
[0326] Further suitable compounds (generally also described as salts or adducts) are melamine sulfate, melamine, melamine borate, oxalates, phosphate prim., phosphate sec. and pyrophosphate sec., melamine neopentyl glycol borate. According to the invention, the molding material preferably does not contain polymeric melamine phosphate (CAS No. 56386-64-2 or 218768-84-4).
[0327] This is understood to mean melamine polyphosphates of 1,3,5-triazine compounds, whose average degree of condensation n is from 20 to 200 and whose 1,3,5-triazine content is from 1.1 mol to 2.0 mol of 1,3,5-triazine compounds selected from the group consisting of melamine, melam, melem, cyanuric acid amide, ammeline, ammeline, 2-ureidomelamine, acetoguanamine, benzoguanamine and diaminophenyltriazine per mole of phosphorus atom. Preferably, the n value of such salts is generally from 40 to 150, and the ratio of 1,3,5-triazine compounds per mole of phosphorus atom is preferably from 1.2 to 1.8. In addition, the pH of a 10% by weight aqueous slurry of the salt prepared according to EP-B1 095 030 is generally greater than 4.5 and preferably at least 5.0. The pH is usually determined by adding 25 g of salt and 225 g of clean water to a 300 ml beaker at 25° C., stirring the resulting aqueous slurry for 30 minutes, and then measuring the pH. The above n value (number average degree of condensation) can be determined by 31P solid-state NMR. JR van Wazer, CF Callis, J. Shoolery and R. Jones, J. Am. Chem. Soc., 78, 5715, 1956 disclosed that the number of adjacent phosphate groups gives a unique chemical shift, which allows a clear distinction between orthophosphates, pyrophosphates and polyphosphates.
[0328] Suitable guanidine salts are
[0329]
[0330] In the context of the present invention, "compounds" are to be understood as meaning not only, for example, benzoguanamine itself and its adducts / salts, but also nitrogen-substituted derivatives and their adducts / salts.
[0331] Also suitable is ammonium polyphosphate (NH4PO3) n , wherein n is about 200 to 1000, preferably 600 to 800, and tris(hydroxyethyl)isocyanurate (THEIC) of formula IV
[0332]
[0333] or with aromatic carboxylic acid Ar(COOH) m wherein Ar represents a monocyclic, bicyclic or tricyclic aromatic six-membered ring system and m is 2, 3 or 4.
[0334] Examples of suitable carboxylic acids include phthalic acid, isophthalic acid, terephthalic acid, 1,3,5-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, pyromellitic acid, benzilic acid, pyromellitic acid, 1-naphthoic acid, 2-naphthoic acid, naphthalene dicarboxylic acid, and anthracenecarboxylic acid.
[0335] According to the process of EP-A 584 567, production is carried out by reaction of tris(hydroxyethyl)isocyanurate with acids, their alkyl esters or their halides.
[0336] Such reaction products are mixtures of monomers and oligoesters, which may also be crosslinked. The degree of oligomerization is generally from 2 to about 100, preferably from 2 to 20. Preference is given to using THEIC and / or its reaction products with phosphorus-containing nitrogen compounds, in particular (NH4PO3) n or mixtures of melamine pyrophosphate or polymerized melamine phosphates. For example, (NH4PO3) n The mixing ratio with THEIC is preferably 90.0 to 50.0:10.0 to 50.0, in particular 80.0 to 50.0:50.0 to 20.0, % by weight, based on the mixture of such compounds.
[0337] Likewise suitable flame retardants are benzoguanidine compounds of the formula V
[0338]
[0339] Therein R, R′ denotes a straight-chain or branched alkyl radical having 1 to 10 carbon atoms, preferably hydrogen, and in particular adducts thereof with phosphoric acid, boric acid and / or pyrophosphoric acid.
[0340] Also preferred are allantoin compounds of formula VI,
[0341]
[0342] wherein R and R' are as defined in formula V, and salts thereof with phosphoric acid, boric acid and / or pyrophosphoric acid, and glycoluril of formula VII or salts thereof with the above acids
[0343]
[0344] wherein R is as defined in Formula V.
[0345] According to DE-A 196 14 424, suitable products are commercially available or obtainable.
[0346] Cyanoguanidine (formula VIII) which can be used according to the invention can be obtained, for example, by reacting calcium cyanamide with carbonic acid, the resulting cyanamide dimerizing at pH 9 to pH 10 to provide cyanoguanidine.
[0347] CaNCN+H2O CO2 → H2N-CN+CaCO3
[0348]
[0349] The commercially available product is a white powder having a melting point of 209 to 211°C.
[0350] Particular preference is given to using melamine cyanurate (e.g. MC25).
[0351] It is also possible to use individual metal oxides such as antimony trioxide, antimony pentoxide, sodium antimonate and similar metal oxides. However, it is preferred to avoid the use of such metal oxides since they are already present in component F. For a description of pentabromobenzyl acrylate and antimony trioxide or antimony pentoxide, reference is made to EP-A 0 624 626.
[0352] Phosphorus (eg red phosphorus) can also be used as a flame retardant. Red phosphorus can be used, for example, in the form of a masterbatch.
[0353] Also considered are dicarboxylic acids of the formula:
[0354]
[0355] in
[0356] R 1 To R 4 independently of one another represent halogen or hydrogen, provided that at least one radical R 1 To R 4 Indicates halogen
[0357] x=1 to 3, preferably 1, 2
[0358] m=1 to 9, preferably 1 to 3, 6, 9, especially 1 to 3
[0359] n=2 to 3
[0360] M = alkaline earth metal, Ni, Ce, Fe, In, Ga, Al, Pb, Y, Zn, Hg.
[0361] Preferred dicarboxylates contain, independently of one another, Cl or Br or H as radical R 1 To R 4 , particularly preferably all radicals R 1 To R4 It is Cl and / or Br.
[0362] As the metal M, Be, Mg, Ca, Sr, Ba, Al, Zn and Fe are preferred.
[0363] Such dicarboxylates are commercially available or can be prepared according to the method described in US 3,354,191.
[0364] Functional polymers can also be used as component E. These can be, for example, flame-retardant polymers.
[0365] These may be, for example, flame retardant polymers. Such polymers are described, for example, in US 8,314,202 and comprise 1,2-bis[4-(2-hydroxyethoxy)phenyl]ethanone repeating units. Another suitable functional polymer for increasing the amount of residual carbon is poly(2,6-dimethyl-1,4-phenylene ether) (PPPO).
[0366] The present invention further relates to a process for preparing a polymer product, preferably comprising the following steps:
[0367] - Converting the polyamide B or polyamide B1 obtainable by the process according to the invention or obtained by this process to obtain a polymer product.
[0368] The process preferably comprises one or all of the additional steps of the process according to the invention for preparing the above-mentioned polyamide B or polyamide B1.
[0369] Preferably, the polymer product is a particle, wire, rod, plate, tube, foil, layer, film, sheet, fiber, filament, coating, extruded and / or molded part, flexible foam, semi-rigid foam and rigid foam. More preferably, the polymer product is an injection molded part.
[0370] Therefore, the present invention more preferably relates to a process for producing a molding, which comprises injection molding a polyamide B or a polyamide B1 or a polyamide composition according to the invention.
[0371] Therefore, the present invention further relates to a polymer product comprising polyamide B or polyamide B1 or polyamide composition according to the present invention, wherein the polymer product is preferably a granule, a wire, a rod, a plate, a tube, a foil, a layer, a film, a sheet, a fiber, a filament, a coating, an extruded and / or molded part, a flexible foam, a semi-rigid foam and a rigid foam. More preferably, the polymer product is an injection molded part.
[0372] Preferably, the invention relates to injection-molded parts comprising a polyamide B or polyamide B1 or a polyamide composition according to the invention.
[0373] The invention further relates to the use of the polyamide B or polyamide or polyamide composition according to the invention for producing a polymer product selected from the group consisting of granules, wires, rods, plates, tubes, foils, layers, films, sheets, fibers, filaments, coatings, extruded and / or molded parts, flexible foams, semi-rigid foams and rigid foams. More preferably, the polymer product is an injection molded part.
[0374] Preferably, the invention relates to the use of the polyamide B or polyamide B1 or polyamide composition according to the invention for producing injection-molded parts.
[0375] Further preferably, the polymer product prepared by the process of the present invention comprises a semi-crystalline or amorphous polyamide or a mixture thereof, preferably one or more components selected from the group consisting of PA 6, PA 66, PA 6 / 66, PA 66 / 6, PA 12, PA 610, PA 46, PA6T / 6, PA 6T / 66, PA 9T, PA 10T, PA 6I / 6T, PA 6T / 6I, PA 6T / 6I / 66, PA 66 / 6T and PA 4T, more preferably one or more components selected from the group consisting of PA 6, PA 66, PA 6 / 66 and PA 66 / 6.
[0376] The polymer product is preferably the following or a portion thereof:
[0377] - automotive parts, preferably cylinder head covers, engine hoods, housings of charge air coolers, cover panels of charge air coolers, air intake pipes, intake manifolds, connectors, gears, fan wheels, cooling water tanks, housings or housing parts of heat exchangers, coolant coolers, charge air coolers, thermostats, water pumps, radiators, fasteners or parts of battery systems for electric vehicles, instrument panels, steering column switches, seats, headrests, center consoles, transmission components, door modules, automotive exteriors of A, B, C or D column covers, spoilers, door handles, exterior mirrors, windshield wipers, windshield wiper protective housings, decorative grilles, cover strips, roof rails, window frames, sunroof frames, antenna panels, headlights and taillights, engine hoods, cylinder head covers, intake manifolds, airbags or cushions;
[0378] - Cloth, preferably shirts, trousers, pullovers, boots, shoes, soles, tights or jackets;
[0379] - an electrical component, preferably an electrical or electronic passive or active component, a printed circuit board, a printed circuit board, a housing component, a foil, a wire, a switch, a plug, a socket, a distributor, a relay, a resistor, a capacitor, an inductor, a bobbin, a lamp, a diode, an LED, a transistor, a connector, a voltage regulator, an integrated circuit (IC), a processor, a controller, a memory, a sensor, a connector, a micro switch, a micro button, a semiconductor, a reflector housing for a light emitting diode (LED), a fastener, a gasket, a bolt, a strip, a slide-in guide, a screw, a nut, a film hinge, a spring hook (snap-on) or a spring tongue for an electrical or electronic component;
[0380] - consumer and / or pharmaceutical products, preferably tennis strings, climbing ropes, bristles, brushes, artificial grass, 3D printing filaments, lawn mowers, zippers, hook and loop fasteners, paper machine fabrics, extrusion coatings, fishing lines, fishing nets, offshore lines and ropes, vials, syringes, ampoules, bottles, sliding elements, spindle nuts, chain conveyors, plain bearings, rollers, wheels, gears, rollers, ring gears, screws and spring dampers, hoses, pipes, cable sheathing, sockets, switches, cable ties, fan wheels, carpets, cosmetic cases or bottles, mattresses, cushions or insulation materials; and / or
[0381] - Packaging for the food industry; preferably mono- or multi-layer blown films, cast films (mono- or multi-layer), biaxially stretched films, laminated films.
[0382] The present invention further relates to the process of the present invention and the polymer product of the present invention, wherein the content of polyamide A in the polymer product is typically 1 wt. % or more, preferably 2 wt. % or more, more preferably 5 wt. % or more, more preferably 15 wt. % or more, more preferably 30 wt. % or more, more preferably 40 wt. % or more, more preferably 60 wt. % or more, more preferably 80 wt. % or more, more preferably 90 wt. % or more, more preferably 95 wt. % or more; and / or
[0383] wherein the content of polyamide B in the polymer product is generally 100 wt % or less, preferably 95 wt % or less, more preferably 90 wt % or less, more preferably 50 wt % or less, more preferably 25 wt % or less, more preferably 10 wt % or less; and
[0384] Preferably wherein said content is determined based on identity preservation and / or segregation and / or mass balance and / or a book and claim chain of custody model, preferably based on mass balance, preferably based on the International Sustainability and Carbon Certification (ISCC) standard.
[0385] The conversion step to obtain the polymer product may comprise one or more synthesis steps and may be carried out by conventional syntheses and techniques well known to the person skilled in the art. The novelty and inventive step of the independent claims are assessed independently of the person skilled in the art who carries out the conversion step from the technical field of depolymerization and / or synthesis and / or production of monomers, polymers and polymer compounds and their further processing (e.g. extrusion, injection molding). Examples of conversion steps are described in "Industrial Organic Chemistry", Volume 3, Wiley-VCH, 1997; ISBN: 978-3-527-28838-0; "Kunststoffhandbuch", all 11 volumes and 17 fascicles, Carl Hanser Verlag, in particular Volume 6, "Polyamide", 1 edition, 1966; "Injection Molding Reference Guide", 4th edition, CreateSpace Independent Publishing Platform, 2011, ISBN: 978-1466407824; WO2008155271 (A1) and WO2013139827 (A1), each of which is incorporated herein by reference.
[0386] Polyamide B, polyamide B1 and the polyamide compositions according to the invention are particularly useful in injection moulding.
[0387] The present invention therefore relates to injection-molded parts comprising polyamide B, polyamide B1 and polyamide compositions according to the invention.
[0388] Examples of injection molded parts according to the present invention are injection molded parts of automobiles, electrical appliances, chemical equipment, machines, etc. Injection molded parts according to the present invention include almost all parts of automobiles, such as engine parts, electrical parts and body parts. Engine parts especially include intake systems and fuel systems, such as engine cylinder head covers, throttle valves, air filter housings, vehicle air horns, vehicle air conditioning hoses, cooling fans and their housings, intake pipes, brake oil tanks and fuel fillers. Body parts especially include automobile fenders, rearview mirror frames, bumpers, dashboards, luggage racks, door handles, wiper brackets, seat belt buckles and various decorative parts in the car. In-car electrical appliances especially include electronically controlled doors and windows, connectors, fresh-keeping boxes, and cable ties.
[0389] The invention further relates to the use of polyamide B, polyamide B1 and polyamide compositions according to the invention for producing injection-molded parts and to a process for producing a molding, which comprises injection molding polyamide B, polyamide B1 and polyamide compositions according to the invention. Examples of suitable injection-molded parts are mentioned above.
[0390] The present invention is further illustrated by the following examples. Example
[0391] Preparation of polyamide B and polyamide composition comprising polyamide B
[0392] Viscosity measurement
[0393] The viscosity number (VN) of the polyamide and polyamide composition according to the invention is measured in sulfuric acid according to EN ISO 307:2019 (0.5% [m / v] polyamide in 96 wt.-% [m / m] sulfuric acid at 25° C.).
[0394] The melt volume flow rate (MVR) of the polyamides according to the invention is measured according to EN ISO 1133-1:2011, procedure A. The material is melted in a heated cylinder and extruded by a piston through a nozzle under a defined pressure into an open space. Test conditions: 275°C / 5kg; the material contains less than 0.05% water. The volume of the extrudate is measured over time (in Table 1 (below), after 5 minutes, 10 minutes and 30 minutes).
[0395] The amino terminal group concentration (AEG [meq / kg]) of the polyamide disclosed in the present invention is measured by potentiometric titration of a polyamide-methanol-phenol solution with an aqueous hydrochloric acid solution. The carboxyl terminal group concentration (CEG [meq / kg]) of the polyamide disclosed in the present invention is measured by titration of a polyamide-benzyl alcohol solution with an ethanolic potassium hydroxide solution.
[0396] Examples 1C, 2C and 3 to 6
[0397] The components mentioned in Table 1 were compounded in the ratios indicated in the table. In inventive examples 3 to 6, the ratio between Ultramid B33 and AH salt was varied. In comparative example 1C no AH salt was used, whereas in comparative example 2 PDMA was used instead of AH salt. A twin screw extruder MC / 26 / 2 from Coperion was used at 50 kg / h, 500 Rpm and 12 zones at a temperature of 300 / 320 / 320 / 320 / 330 / 330 / 330 / 330 / 330 / 330 / 330 / 330°C.
[0398] All additives were added to the cold feed (glass fibers in zone 5).
[0399] Table 1
[0400]
[0401] Only in the examples according to the invention is a reduction in the viscosity number VN achieved such that the polyamide composition is suitable for injection molding and at the same time a significant increase in the MVR over time is avoided.
[0402] *Comparative Example
[0403] 1) Ultramid B33 (i.e. Ultramid B33 01) is a medium viscosity polyamide 6 grade from BASF SE;
[0404] 2) From Nippon Electric Glass HP 3610;
[0405] 3) N,N'-ethylenebisstearamide from Lonza;
[0406] 4) 80% containing 20% CuI / KI (1 / 3) B27; B27 is a low-viscosity polyamide 6 grade from BASF SE;
[0407] 5) Contains 30% carbon black from Cabot Corporation 880 from LyondellBasell 70% 1800H; Lupolen 1800H is a low-density polyethylene resin;
[0408] 6) Hexamethylenediamine adipate (salt of adipic acid and hexamethylenediamine)
[0409] 7) Pyromellitic dianhydride
Claims
1. A method for producing a polyamide B, comprising melt mixing a polyamide A with a salt C of a diacid and a diamine, wherein the polyamide B has a viscosity value measured in sulfuric acid according to EN ISO 307:2019 which is lower than that of the polyamide A, and wherein in polyamide B, the ratio of the amino terminal group concentration of polyamide B to the amino terminal group concentration of polyamide A measured by potentiometric titration of a polyamide-methanolphenol solution with an aqueous hydrochloric acid solution to the ratio of the carboxyl terminal group concentration of polyamide B to the carboxyl terminal group concentration of polyamide A measured by titration of a polyamide benzyl alcohol solution with an ethanolic potassium hydroxide solution is 0.8 to 1.
2.
2. The method according to claim 1, wherein the ratio of the concentration of amino terminal groups of polyamide B measured by potentiometric titration of a polyamide-methanol phenol solution with aqueous hydrochloric acid to the concentration of carboxyl terminal groups of polyamide B measured by titration of a polyamide benzyl alcohol solution with ethanolic potassium hydroxide is ≥ 0.2, preferably ≥ 0.40, more preferably ≥ 0.
70.
3. The process according to claim 1 or 2, wherein the salt C of diacids and diamines is present in an amount of 0.01 to 1% by weight, preferably 0.1 to 0.9% by weight, based on the polyamide A.
4. The process according to any one of claims 1 to 3, wherein the salt C of a diacid and a diamine is hexamethylenediamine adipate.
5. The method according to any one of claims 1 to 4, wherein the viscosity value of polyamide A is 120 cm 3 / g to 250cm 3 / g, preferably 150cm 3 / g to 220cm 3 / g, more preferably 170cm 3 / g to 210cm 3 / g.
6. The method according to any one of claims 1 to 5, wherein the viscosity value of polyamide B is 80 cm 3 / g to 200cm 3 / g, preferably 100cm 3 / g to 180cm 3 / g, more preferably 120cm 3 / g to 160cm 3 / g.
7. The method according to any one of claims 1 to 6, wherein the polyamide A is a semi-crystalline or amorphous polyamide or a mixture thereof, preferably selected from the group consisting of PA 6, PA 66, PA 6 / 66, PA 66 / 6, PA 12, PA 610, PA 46, PA 6T / 6, PA 6T / 66, PA 9T, PA 10T, PA 6I / 6T, PA 6T / 6I, PA 6T / 6I / 66, PA 66 / 6T and The invention further comprises one or more components selected from the group consisting of PA 4T, more preferably one or more components selected from the group consisting of PA 6, PA 66, PA 6 / 66 and PA 66 / 6.
8. The method according to any one of claims 1 to 7, wherein the polyamide A comprises post-industrial and / or post-consumer waste, preferably from an extrusion process selected from the group consisting of blow molding, film extrusion, tube extrusion, sheet extrusion, fiber spinning and mixtures thereof.
9. The process according to any one of claims 1 to 8, wherein the polyamide A consists of post-industrial and / or post-consumer waste.
10. The process according to any one of claims 1 to 9, wherein the melt mixing is carried out in the presence of fillers (D) and / or further additives (E).
11. A method for preparing a polymer product, the method preferably comprising the steps according to any one of claims 1 to 10, the method comprising the following steps: - converting the polyamide B obtainable by or obtained by the process according to any one of claims 1 to 10 to obtain the polymer product, wherein the polymer product is preferably a granule, a wire, a rod, a plate, a tube, a foil, a layer, a film, a sheet, a fiber, a filament, a coating, an extruded and / or molded part, a flexible foam, a semi-rigid foam and / or a rigid foam.
12. The method according to claim 15, wherein the content of the polyamide B in the polymer product is 1 wt% or more, preferably 2 wt% or more, more preferably 5 wt%. % or more, more preferably 15 wt % or more, more preferably 30 wt % or more, more preferably 40 wt % or more, more preferably 60 wt % or more, more preferably 80 wt % or more, more preferably 90 wt % or more, more preferably 95 wt % or more; and / or wherein the content of the polyamide B in the polymer product is 100 wt % or less, preferably 95 wt % or less, more preferably 90 wt % or less, more preferably 50 wt % or less, more preferably 25 wt % or less, more preferably 10 wt % or less; and Preferably wherein said content is determined based on identity preservation and / or segregation and / or mass balance and / or a book and claim chain of custody model, preferably based on mass balance, preferably based on the International Sustainability and Carbon Certification (ISCC) standard.
13. A polyamide B obtained by the process according to any one of claims 1 to 10, wherein the ratio of the amino terminal group concentration of polyamide B measured by potentiometric titration of a polyamide-methanol phenol solution with an aqueous hydrochloric acid solution to the carboxyl terminal group concentration of polyamide B measured by titration of a polyamide benzyl alcohol solution with an ethanolic potassium hydroxide solution is preferably ≥ 0.2, more preferably ≥ 0.40, most preferably ≥ 0.
70.
14. A polyamide B1, which consists of: c) 99.00% to 99.99% by weight, preferably 99.10% to 99.90% by weight, of a polyamide B* formed from units selected from one or more diamines in combination with one or more diacids, one or more lactams and mixtures thereof, and d) 0.01 to 1% by weight, preferably 0.1 to 0.9% by weight, of units derived from the diacids and diamines which form the salt C, wherein the units derived from the diacid and the diamine forming the salt C are different from the units forming the polyamide B*. 15 . Polyamide B1 according to claim 14 , wherein the diacid and the diamine forming the salt C are adipic acid and hexamethylenediamine.
16. Polyamide B according to claim 13 or polyamide B1 according to claim 14 or 15, wherein the viscosity of polyamide B is 80 cm 3 / g to 200cm 3 / g, preferably 100cm 3 / g to 180cm 3 / g, more preferably 120cm 3 / g to 160cm 3 / g.
17. The polyamide B1 according to any one of claims 14 to 16, wherein the polyamide B* is a semi-crystalline or amorphous polyamide or a mixture thereof, preferably one or more components selected from the group consisting of PA 6, PA 12, PA 610, PA 46, PA 6T / 6, PA 9T, PA10T, PA 6I / 6T, PA 6T / 6I and PA 4T, more preferably PA 6.
18. A polyamide composition comprising: (i) polyamide B according to claim 13 or 16 or polyamide B1 according to any one of claims 14 to 17; and (ii) optionally a filler material (D) and (iii) optionally at least one further additive (E); At least one filler material (D) or another additive is present therein.
19. A polymer product comprising a polyamide B according to claim 13 or 16 or a polyamide B1 according to any one of claims 14 to 17 or a polyamide composition according to claim 18, wherein the polymer product is preferably a granule, a wire, a rod, a plate, a tube, a foil, a layer, a film, a sheet, a fiber, a filament, a coating, an extruded and / or molded part, a flexible foam, a semi-rigid foam and / or a rigid foam.
20. Use of the polyamide B according to claim 13 or 16 or the polyamide B1 according to any one of claims 14 to 17 or the polyamide composition according to claim 18 for producing a polymer product selected from granules, wires, rods, plates, tubes, foils, layers, films, sheets, fibers, filaments, coatings, extruded and / or molded parts, flexible foams, semi-rigid foams and rigid foams.
Citation Information
Patent Citations
Thermoplastic molded mass, useful for the preparation of fibers, molded bodies or foil, comprises a thermoplastic polyamide, a high- or hyper- branched polyester in an acid or alcohol component containing aromatic core, and an additive
DE102009011668A1
process for the production of polyamides
DE10313681A1
synergistic flame retardant combination for polymers
DE19614424A1
Flame retardant combination
DE19933901A1
flame retardant combination for thermoplastic polymers I
DE19960671A1